A risk-factor profile for chronic lifestyle diseases in three rural Free State towns - Sanet van Zyl; Lynette J. van der Merwe; Corinna M. Walsh; Francois C. van Rooyen; Hendrik J. van Wyk; Andries J. Groenewald (South African Family Practice)
Background: Chronic diseases of lifestyle account for millions of deaths each year globally. These diseases share similar modifiable risk factors, including hypertension, tobacco smoking, diabetes, obesity, hyperlipidaemia and physical inactivity. In South Africa the burden of noncommunicable disease risk factors is high. To reduce or control as many lifestyle risk factors as possible in a population, the distinct risk-factor profile for that specific community must be identified. Therefore, the aim of this study was to assess the health status in three rural Free State communities and to identify a distinct risk-factor profile for chronic lifestyle diseases in these communities.